KEDUDUKAN FIQIH DALAM STRUKTUR ILMU ISLAM: ANALISIS ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS - Jazlynne Attia Pradnya Ubaedi; Alyya Zulfa Alika; Claudya Amalia Putri; Darius Muammar Alifi; Muhamad Khalfan Ibrahim (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study aims to philosophically analyze the position of Fiqh within the structure of Islamic knowledge, specifically regarding the duality of Islamic Law between Sharia (which is absolute) and Fiqh (which is the product of Ijtihad, or relative). This research employs the philosophy of science approach, focusing on three pillars: ontology (nature), epistemology (method), and axiology (value). Ontologically, Fiqh serves as a bridge connecting the metaphysical reality of Divine law with empirical human actions, thereby rejecting Western reductionism. Epistemologically, Fiqh is validated through the integrative methodology of Ijtihad (combining reason and revelation), consequently producing a plurality of laws (ikhtilaf) in subsidiary matters (furu'iyyah). Axiologically, Fiqh finds its justification in the ultimate objective, which is the Maqasid Sharia (the realization of public benefit). It is concluded that Fiqh occupies a central position as a dynamic and adaptive discipline in social and transactional matters (muamalah), yet remains firmly rooted in the foundational principles of Tauhid guaranteed by the Sharia, thereby providing a significant contribution to the holistic structure of Islamic knowledgeKeywords : Axiology, Epistemology, Fiqh, Maqasid Sharia, Ontology, Philosophy of Law, Sharia.